#1
I understand the basics of finding the gradient of a line but am getting confused with this particlar question. If you can explain how to get to the answer, that'd be great. Question: Find the gradient of the line joining the pair of points with coordinates (p+3,p-3),(2p+4,-p-5) Answer: -2 I've been using the equation of Y2-Y1/X2-X1
0
1 week ago
#2
(Original post by Emily Josephine)
I understand the basics of finding the gradient of a line but am getting confused with this particlar question. If you can explain how to get to the answer, that'd be great. Question: Find the gradient of the line joining the pair of points with coordinates (p+3,p-3),(2p+4,-p-5) Answer: -2 I've been using the equation of Y2-Y1/X2-X1
It's just a question of plugging in the values, and then simplifying.

If you've done it correctly, you can factor out "p+1" in your working.

If not, post your working so far.
#3
Here is my working:

Y2 - Y1 = (-p-5)-(p-3) = -p-5-p-3 = -2p-8
X2 - X1 = (2p+4)-(p+3) = 2p+4-p+3 = p+7

so then...

-2p-8 / p+7 = ????

I'm lost and can't see how it equals -2
I know I must have gone wrong, just can't get my head around it
0
1 week ago
#4
Couple of things:
-5 - (-3) = -5 + 3 = -2
4 - (+3) = 4 - 3 = 1
0
#5
Thank you! That makes sense! I just expanded the brackets wrong. Just to check this is now my workings:
-2p-2/1p+1 = -2-2/2 = -4/2 = -2

I hope that's right... But feel I've over complicated it. Is there a simpler way?
0
1 week ago
#6
(Original post by Emily Josephine)
Thank you! That makes sense! I just expanded the brackets wrong. Just to check this is now my workings:
-2p-2/1p+1 = -2-2/2 = -4/2 = -2

I hope that's right... But feel I've over complicated it. Is there a simpler way?
The p can't just disappear
-2p - 2 = -2(p+1)
1p+1 = (p+1)
The (p+1) factor cancels in both top and bottom.
0
1 week ago
#7
(Original post by Emily Josephine)
Thank you! That makes sense! I just expanded the brackets wrong. Just to check this is now my workings:
-2p-2/1p+1 = -2-2/2 = -4/2 = -2

I hope that's right... But feel I've over complicated it. Is there a simpler way?
No that’s not right, as you seem to have set p = 1 with no justification.
(-2p - 2)/(p + 1) = -2(p + 1)/(p + 1) then cancel (p + 1) from top and bottom.
0
#8
Oh right I see. Thank you so much for your help!
0
X

new posts
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### University open days

• Solent University
Mon, 25 Mar '19
• Cardiff University
Wed, 27 Mar '19
• University of Portsmouth
Wed, 27 Mar '19

### Poll

Join the discussion

#### Where do you need more help?

Which Uni should I go to? (149)
18.53%
How successful will I become if I take my planned subjects? (79)
9.83%
How happy will I be if I take this career? (136)
16.92%
How do I achieve my dream Uni placement? (114)
14.18%
What should I study to achieve my dream career? (79)
9.83%
How can I be the best version of myself? (247)
30.72%